Design of a Prototype of a Medical Check Up Information System for ASN in Karawang Regency Using the Waterfall Method - Hatim Alwan; Bambang Setiaji; Endang Suryadi (Green Publisher Indonesia, 2026)
The State Civil Apparatus (ASN) is an important element in running the wheels of government. To maintain the performance and productivity of ASN, excellent health conditions are needed through periodic medical check-ups. This research aims to design and develop a web-based MCU information system prototype to automate and integrate the entire process. The study uses the waterfall method in software development, which includes five main stages: needs analysis, system design, prototype implementation, testing, and documentation. The effectiveness of this web-based medical check-up information system is generally at a very good level, with a percentage value of 96%. The highest observation aspect is the accuracy of data conveyed between units, at 100%, followed by an easy-to-understand web display at 98.6%. The research resulted in a prototype of the Medical Check Up information system, which includes online registration features, examination schedule management, filling and storing medical data, and reporting the results of ASN examinations. This system is designed to be responsive and easy to use by health workers and civil servants. Evaluation of the prototype showed that the system can speed up work processes, reduce recording errors, and provide centralized health data. The design of the prototype of the Medical Check Up information system has been proven to increase efficiency and accuracy in implementing MCU for ASN in Karawang Regency.